Spectrophotometric method development and validation for gliclazide quantitation in tablets - Leleka, L. H.; Vasіuk, S. O.; Лелека, Лідія Геннадіївна; Васюк, Світлана Олександрівна (My University, 2022)
Objective: A new spectrophotometric method for the gliclazide quantitation in dosage forms has been developed Material and Method: The subjects of the study were modified-release tablets ("Diaglizide" 80 mg, "Diaglizide MR" 60 mg, "Diaglizide MR" 30 mg, "Diabeton" MR 60 mg, "Gliklada" 60 mg). As a reagent, bromocresol green in acetone was used. Analytical equipment: spectrophotometer Specord 200, electronic scales АВТ-120-5DM. Result and Discussion: It has been experimentally determined that gliclazide reacts with bromocresol green in acetone medium at room temperature to form a yellow product with maximum absorption at 411 nm. The method was validated for linearity, accuracy, precision, and robustness. The agent’s optimal concentration was established and the stability of the investigated solutions was checked by measuring their optical density for 30 minutes. Subordination of Beer's law is observed in the range of 62.00 - 94.00 mg/100 ml. The limit of detection is 4.02∙10-6 g/ml, which indicates a high sensitivity of the reaction. The proposed method is validated according to the requirements of the State Pharmacopoeia of Ukraine. The results of the study show that the developed method is simple and affordable to implement and can be used to determine gliclazide in drugs in laboratories for quality control of dosage forms.
Leleka L. - https://orcid.org/0000-0002-3957-6264; Vasyuk S. - https://orcid.org/0000-0002-1569-9374.
Keywords: Вromocresol green; gliclazide; spectrophotometry